The prevalence of temporomandibular dysfunction in patients with spine pain - Ribeiro, Diogo Suriani; Silva, Brayner Gomes e; Oliveira, Nayara da Silva; Almeida, Amanda Oliveira; Santos, Maikon Gleibyson Rodrigues dos; Silva, Luiz Guilherme Cardoso da; Lemos, Thiago Vilela (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The Temporomandibular disfunction (TMD) is a composite of signs and symptoms manifested as a consequence of disorders in the stomatognathic system. Temporomandibular Joint Disorders can cause problems in the cervical and lumbar spine and vice versa. Objective: To identify the prevalence of TMD in people with pain in the spine. Method: It is an analytical quantitative transversal study. Study participants were 60 volunteers of both sexes, from four orthopedic physical therapy clinics, with patients being treated for painful conditions vertebral in Goiânia - GO. Questionnaire Anamnesic Fonseca (1994) was used to capture and interpret data as well as verification of temporomandibular dysfunction to characterize the severity of TMD symptoms. The software used for statistical analysis was the BioEstat 5.0. Results: Of the 60 subjects assessed, 70% had at least one diagnosis of dysfunction. Of these, 52.4% had mild TMD, 33.3% had moderate and 14.2% had severe. Of individuals diagnosed with TMD, 30 are female and 12 male. Conclusion: Although no significance found in the statistical tests, we can demonstrate the relevance percentage in degree of severity in various regions of the spine, highlighting the cervical region, where all patients with pain at this location had some degree of TMD, and low back pain as the symptom most found in research, whether present or not some degree of TMD.